Enhancing the mechanical and hydromechanical behaviors of mudstone soils using sugarcane press mud. (May 2023) - Gumanta, Febi Satria; Ghadr, Soheil; Chen, Chieh-Sheng; Liu, Chih-Hsuan; Hung, Ching; Assadi-Langroudi, Arya
Abstract: Geological hazards, such as landslides and soil erosion, are frequently found in regions where mudstone soils are prevalent. These soils can also present challenges for the construction of infrastructure, including roads, railways, and other facilities. While various methods exist for addressing the mechanical and hydromechanical properties of mudstone soils, the reuse of waste materials may be a cost-effective alternative. This study presents the effect of press mud, a by-product of sugar purification, as an alternative material for improving the performance of mudstone soils. Unconfined compressive strength tests were conducted to evaluate the mechanical properties of untreated and press mud-treated mudstone soils. In addition, free swell tests, one-dimensional consolidation tests, and three-dimensional volumetric shrinkage tests were performed to investigate the hydromechanical properties of the soils. These tests provided insights into the behavior of the mudstone soils under various conditions. In addition, microstructural analysis such as X-ray diffraction, X-ray fluorescence, Fourier-transform infrared spectroscopy, and scanning electron microscopy were performed to identify the soil improvement mechanisms. The results demonstrated that press mud can act as a binder and help enhance the peak and postpeak strengths of mudstone soils. The swelling and shrinkage characteristics improved when it was treated with press mud; however, the inclusion of press mud slightly increased the compressibility of mudstone soils. According to microstructural analysis, the formation of extra cementitious gels helped enhance the mudstone soils performance. These findings offer promising and environmentally friendly options for effectively treating mudstone soils and address the needs of engineers seeking sustainable solutions.